2019
DOI: 10.1002/clen.201800202
|View full text |Cite|
|
Sign up to set email alerts
|

Response of Soil Nematode Community to Phosphorous Amendment in a Subalpine Spruce Plantation

Abstract: An appropriate management practice is indispensable to the restoration of ecological functioning, particularly in ecologically vulnerable regions. The short-term effects of phosphorous (P) amendment on community structure and function of soil micro-food webs in a subalpine spruce (Picea asperata) plantation are examined. Experimental plots are established and treatments are performed with P addition at two levels: Low P (LP) input of 5 g m À2 per year and high P (HP) input 30 g m À2 per year as NaH 2 PO 4 Á 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
2
0
2
Order By: Relevance
“…In this study, the phosphorus application rate was 112.5 g m −1 , which is enough to cause damage to nematodes. Research evidence suggests that phosphorus addition affects soil nematodes primarily by changing soil pH and total phosphorus content (Wei et al, 2012;Yang et al, 2019). In summary, the results suggest that the effect of phosphorus on soil nematode communities in soybean farmland ecosystems is mediated by changes in soil pH, total phosphorus, and ammonium nitrogen.…”
Section: Effects Of Phosphorus Addition On Soil Nematode Communitiesmentioning
confidence: 79%
See 1 more Smart Citation
“…In this study, the phosphorus application rate was 112.5 g m −1 , which is enough to cause damage to nematodes. Research evidence suggests that phosphorus addition affects soil nematodes primarily by changing soil pH and total phosphorus content (Wei et al, 2012;Yang et al, 2019). In summary, the results suggest that the effect of phosphorus on soil nematode communities in soybean farmland ecosystems is mediated by changes in soil pH, total phosphorus, and ammonium nitrogen.…”
Section: Effects Of Phosphorus Addition On Soil Nematode Communitiesmentioning
confidence: 79%
“…The possible mechanism of influence of nitrogen addition significantly increasing the relative abundance of plant parasites was that nitrogen fertilizer addition promotes plant growth and significantly increased aboveground plant biomass (Liang et al, 2009), thereby providing more resources for plant parasite nematodes (Bongers T. and Bongers M. et al, 1998). It has also been shown that phosphorus addition affected soil nematodes mainly by changing soil pH and total phosphorus content (Wei et al, 2012;Yang et al, 2019). In farmland ecosystems, the application of nitrogen and phosphorus fertilizers increased soil nematode abundance, genus richness, maturity index (MI), and structural index (SI) (Niu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Se ha demostrado que la deposición de N induce un enriquecimiento orgánico en el suelo que incrementa la presencia de nematodos bacterívoros oportunistas y herbívoros, reduciendo la complejidad de la comunidad (Shaw et al 2019), pero, en nuestro caso, el efecto positivo de los tratamientos con nitrógeno sobre la Huella Metabólica de los bacterívoros no se vio acompañada por un cambio estructural en la comunidad. En otros tipos de ecosistemas la deposición de N puede ejercer una influencia directa y positiva sobre los nematodos fungívoros y bacterívoros (Liu et al 2020), mientras que, en los bosques subalpinos, la adición de P al suelo tuvo un efecto claramente negativo sobre la comunidad (Yang et al 2019). En mayor consonancia con nuestros resultados, otros trabajos previos sólo han encontrado respuestas indirectas de la fauna edáfica a la deposición de nutrientes, mediadas por las alteraciones producidas por la deposición de nutrientes en la estructura de la vegetación (Mitchell et al 2016).…”
Section: Discussionunclassified
“…La limitada información previa muestra que, en bosques templados, una deposición experimental de N puede incrementar las abundancias de algunos nematodos fungívoros y bacterívoros (Liu et al 2020), aunque sus efectos son muy dependientes de la existencia de vegetación arbórea y del tipo de bioma afectado (Liu et al 2021). A largo plazo, la adición de N en un bosque subalpino aumentó las abundancias de nematodos, pero redujo su riqueza, diversidad y madurez (Shaw et al 2019), mientras que la adición de P redujo las abundancias de predadores y omnívoros (Yang et al 2019). Otros estudios, sin embargo, no han encontrado efectos significativos de la deposición experimental de N en los nematodos del suelo, pese a encontrar efectos negativos de la deposición sobre las abundancias de bacterias, más sensibles a la deposición que los hongos (Shao et al 2018).…”
Section: Figure 1 A) Digital Iberian Peninsula Climatic Atlasunclassified